Water vapor mixing ratio from MLS/GEOSCCM/trajectory model simulations and tropical average time series of regressors from ERAi/MERRA-2/GEOSCCM, link to netCDF files - Hao Ye; Andrew Dessler (PANGAEA, 2018)
The zip contains the following files: MLS_traj_water_vapor_100hpa.nc and GEOSCCM_traj_water_vapor_100hpa.nc are netCDF files of the water vapor mixing ratio from MLS/GEOSCCM/trajectory model simulations. All data are lon/lat/time at 100 hPa in parts per million by volume. Reanalyses_regressors.nc and GEOSCCM_regressors.nc contain the tropical average time series of regressors from ERAi/MERRA-2/GEOSCCM. These regressors are indices for BDC, tropospheric temperature and/or QBO.
Supplement to: Ye, Hao; Dessler, Andrew; Yu, Wandi (2018): Effects of convective ice evaporation on interannual variability of tropical tropopause layer water vapor. Atmospheric Chemistry and Physics, 18(7), 4425-4437, https://doi.org/10.5194/acp-18-4425-2018